2010
DOI: 10.1001/archneurol.2010.203
|View full text |Cite
|
Sign up to set email alerts
|

Neuromyelitis Optica Treatment

Abstract: Patients: Thirty-six patients with relapsing-remitting optic-spinal disease; long, extending spinal cord lesions; and brain magnetic resonance images not meeting Barkhof criteria for multiple sclerosis, thus fulfilling the 1999 and 2006 criteria for neuromyelitis optica. Patients were followed up from 1994 to 2007.Main Outcome Measures: Relapses and accumulation of disability.Results: Mean follow-up time was 47.2 months and mean ageatonsetwas32.3years.Sixty-fourtreatmentswereimple-mentedin36patients,whichinclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
76
1
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(89 citation statements)
references
References 33 publications
6
76
1
6
Order By: Relevance
“…Several studies including a total of almost 400 patients have shown that AZA reduces the ARR, sometimes associated with improvement of neurological disability [17,[74][75][76][77][78][79][80]. A retrospective study evaluating classical NMO and patients with AQP4-IgG-positive NMOSD reported a decrease in the mean ARR from 2.18 to 0.64 in 70 patients treated with AZA for >1 year, with or without concomitant corticosteroid therapy [77].…”
Section: Azamentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies including a total of almost 400 patients have shown that AZA reduces the ARR, sometimes associated with improvement of neurological disability [17,[74][75][76][77][78][79][80]. A retrospective study evaluating classical NMO and patients with AQP4-IgG-positive NMOSD reported a decrease in the mean ARR from 2.18 to 0.64 in 70 patients treated with AZA for >1 year, with or without concomitant corticosteroid therapy [77].…”
Section: Azamentioning
confidence: 99%
“…Adjunctive therapy of AZA [17,75,77,79], MMF [79,83], MTX [85][86][87], ciclosporine A [88], and tacrolimus [89] with oral corticosteroids have all been reported to be (partly) effective and safe in NMOSD. In breakthrough disease intermittent TPE might be added to immunosuppressive treatment [8,98], but usually escalation to a biological is preferable.…”
Section: Combination Therapies Of Immunosuppressantsmentioning
confidence: 99%
“…In addition to PLEX and IVIg, uncontrolled case series suggest that use of immune suppressants including CTX (idiopathic transverse myelitis, SLE) (D'Cruz et al, 2004;Greenberg et al, 2007), rituximab (NMO) Jacob et al, 2008a), and azathioprine (NMO), (Bichuetti et al, 2010) might be helpful.…”
Section: Treatmentmentioning
confidence: 99%
“…All patients received regular preventive therapies recommended at the time they were seen, which included, corticosteroids, azathioprine, cyclophosphamide, methotrexate, plasma exchange and IV immunoglobulin 7 . This work is part of an continuous observational project at the Universidade Federal de São Paulo, has received local ethic committee approval and patients have given informed consent for retrospective and prospective data collection.…”
mentioning
confidence: 99%
“…Since this analysis comes from a historical cohort, information on vitamin D levels was not available and this should be prospectively evaluated together with other factors, such as the association to common infection and physical and psychological stress factors. Most of these patients received regular immunosuppressive treatment with azathioprine with or without prednisone as part of our regular treatment protocol, with 76% response 7 , and thus treatment biases is expected to not have influenced these results.…”
mentioning
confidence: 99%